Prostate-specific membrane antigen can promote in vivo osseous metastasis of prostate cancer cells in mice - Zhao,Liang-Yun (2012)
Reports remain insufficient on whether and how prostate-specific membrane antigen (PSMA) can influence in vivo osseous metastasis of prostate cancer (PCa). In the present study, the authors induced stable expression of PSMA in mouse PCa cell line RM-1. In vivo osseous metastasis was induced in 37 6-week-old female C57BL/6 mice weighing 22.45 ± 0.456 g. RM-1 cells were actively injected into the femoral bone cavity, leading to bilateral dissymmetry of bone density in the femoral bone. Tumor cells were also detected in bone tissue by pathological examination. The impact on bone density was demonstrated by the significant difference between animals injected with RM-PSMA cells (0.0738 ± 0.0185 g/cm²) and animals injected with RM-empty plasmid cells (0.0895 ± 0.0241 g/cm²). The lytic bone lesion of the RM-PSMA group (68.4%) was higher than that of the control group (27.8%). Immunohistochemistry showed that the expression of both vascular endothelial growth factor (VEGF) and matrix metalloproteinase-9 (MMP-9) was distinctly higher in the RM-PSMA group than in the control group, while ELISA and Western blot assay indicated that VEGF and MMP-9 were higher in the RM-PSMA group compared to the control group (in vitro). Thus, the present study proposed and then confirmed for the first time that PSMA can promote in vivo osseous metastasis of PCa by increasing sclerotic destruction of PCa cells. Further analyses also suggested that PSMA functions positively on the invasive ability of RM-1 by increasing the expression of MMP-9 and VEGF by osseous metastases in vivo